Factors influencing extended hospital stay in patients undergoing metastatic spine tumour surgery and its impact on survival. (October 2018) - Kumar, Naresh; Patel, Ravish Shammi; Wang, Samuel Sherng Young; Tan, Joel Yong Hao; Singla, Aditya; Chen, Zhaojin; Ravikumar, Nivetha; Tan, Amanda; Kumar, Nandika; Hey, Dennis Hwee Weng; Prasad, Samuel Vara; Vellayappan, Balamurugan
Highlights: Retrospective review, 220 patients undergoing MSTS. Median LOS = 7 days; eLOS is defined as >75th percentile of LOS, which was ≥11 days. Metastases from breast, prostate and lung have higher risk of eLOS. eLOS associated with: post-operative complications and/or Instrumentation >9 levels. Patients with eLOS showed reduced survival. Abstract: Metastatic spine tumour surgeries (MSTS) are indicated for preservation or restoration of neurological function, to provide mechanical stability and pain alleviation. The goal of MSTS is to improve the quality of life of the patients with spinal metastases and rarely for oncological control which is usually achieved by adjuvant therapies. Hence outcome measures such as length of stay (LOS) and rate of complications after MSTS are important indicators of quality but there is limited literature evidence for the same. We carried out a retrospective study to determine the incidence and the factors influencing normal (nLOS) and extended length of stay (eLOS) after MSTS. Data of 220 consecutive patients who underwent MSTS between 2005 and 2015 were retrieved from hospital electronic records. The preoperative, intraoperative and postoperative variables, discharge destinations as well as socioeconomic factors were analyzed. eLOS defined as positive when the LOS exceeded the 75th percentile for this cohort, was the key outcome indicator. Univariate and multivariate logistic regression analyses were performed to determine the predictive factors of eLOS. The overall median LOS was 7 days (1–30 days) and 55 patients had eLOS (LOS ≥ 11 days). Multivariate analysis revealed that significant variables independently associated with eLOS were instrumentation >9 spinal segmental levels (OR 2.89, 95% CI 1.1–7.5, p = 0.032) and presence of postoperative complications (OR 3.68, 95% CI 1.85–7.30, p < 0.001). Metastatic tumours other than breast, prostate and lung have lesser risk of eLOS (OR 0.31, 95% CI 0.14–0.70, p = 0.004). Survival estimates show that patients with eLOS have shorter survival than patients with nLOS (Crude HR 1.81, 95% CI 1.13–2.89, p = 0.003).